The Effect of Plant Geographical Location and Developmental Stage on Root-Associated Microbiomes of Gymnadenia conopsea - Lin, Min; Xiong, Hui; Xiang, Xuechuan; Zhou, Zelin; Liang, Lifeng; Mei, Zhinan (Frontiers in Microbiology, 2020)
Gymnadenia conopsea (L.) R. Br. is an important perennial terrestrial photosynthetic orchid species whose microbiomes are thought to play an important role in promoting its growth and health. However, the assemblage of G. conopsea root-associated microbial communities is poorly understood. The compositions of fungal and bacterial communities from the roots and corresponding soil samples of G. conopsea across distinct biogeographical regions from two significantly different altitudes were characterized at the vegetative and reproductive growth stages. The geographical location, developmental stage and compartment were factors contributing to microbiome variation in G. conopsea. Predominant fungal taxa include Ascomycota, Basidiomycota, Mortierellomycota and Chytridiomycota, whereas Proteobacteria, Bacteroidetes, Acidobacteria, Actinobacteria, Verrucomicrobia, Chloroflexi, TM7 and Planctomycetes were predominant bacterial taxa. Using G. conopsea as a model, we report a comprehensive analysis of the structural and functional composition of the G. conopsea root-associated microbiomes. Contrary to previous studies, biogeography was the main factor influencing the microbial community in this study. Besides, compartment and developmental stage should also be considered to analyze the variation of microbiota composition. Although the microbial composition varied greatly by location, the symbiotic microorganisms of G. conopsea still have certain specificity. This study offers an abundant knowledge of G. conopsea root-associated microbiomes and lends guidelines to better understanding the factors determining the diversity and composition of fungal/bacterial communities associated with orchids. Our results also laying a foundation for harnessing the microbiome for sustainable G. conopsea cultivation. Moreover, these results might be generally applicable to other Orchidaceae plants.